Indonesian medicinal plants an index, 1962-1982 - Sukardjo, Djuhriah; Faderon, Rosalie B.; Castillo, Amorita V. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1983)
The descriptive method was used in this study. Manuals of plants were used to determine the scientific names of the plants.
The purpose of the study was to develop an index to books, theses, research reports, and periodical articles on medicinal plants available in the four libraries of the National Biological Institute, written in English or Bahasa Indonesia, and published or unpublished between 1962 and 1982.
The descriptive method was used in this study. Manuals of plants were used to determine the scientific names of the plants.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Botany, Medical -- Indexes. -- Indonesia